Affirmative Mental Health Care for Transgender and Gender Diverse Youth A Clinical Guide (Springer International Publishing, 2018)
This unique resource offers an in-depth, comprehensive look at different types of mental health needs of transgender and gender diverse youth, how these intersect with gender identity, gender expression, and sexual orientation, and provides practical information on how to ethically, responsibly, and sensitively care for these patients. Affirmative Mental Health Care for Transgender and Gender Diverse Youth: A Clinical Guide begins with three introductory chapters which contain practical information regarding assessment, psychological interventions, and the potential medical and surgical interventions that are indicated for youth with gender identity concerns. The remaining chapters are illustrated by multiple cases build around overarching chapter themes. Each case chapter opens with broad questions applicable to clinical practices, while the cases themselves focus on a particular co-occuring mental health condition. The case chapters are structured with intersectionality in mind, including elements of ethnic, racial, and cultural diversity, and the patients range over the full developmental spectrum, from pre-pubertal children to older adolescents. Chapter cases range in complexity as well, to provide readers with the tools they need to evaluate patients, and to assist in the decision of which presenting factors to prioritize in treatment at which time. Ending each chapter are clinical take-home messages, closing with additional practical knowledge that can be applied to other cases providers may see in their own practices. Written by expert clinicians in the field, Affirmative Mental Health Care for Transgender and Gender Diverse Youth: A Clinical Guide is an ideal resource not only for child and adolescent psychiatrists, but for clinicians across all mental health disciplines working with gender non-conforming youth, and who are interested in providing informed, affirmative, and intersectional care.